1
$\begingroup$

How to subtract the two equations. That is, the left subtraction of the two equations is equal to the right subtraction of the equation

Continue to the previous question, how to perform the term shift deformation?

eq1 = x1^2/a^2 + y1^2/b^2 == 1;
eq2 = x2^2/a^2 + y2^2/b^2 == 1;
SubtractSides[eq1, eq2] // FullSimplify

get the result:

((x1 - x2) (x1 + x2))/a^2 + ((y1 - y2) (y1 + y2))/b^2 == 0

The problem now is how to shift the above results to get this result:

((y1 - y2) (y1 + y2))/((x1 - x2) (x1 + x2)) == - b^2/a^2
$\endgroup$

2 Answers 2

3
$\begingroup$

This is your equation:

eqA = ((x1 - x2) (x1 + x2))/a^2 + ((y1 - y2) (y1 + y2))/b^2 == 0;

Try the following:

eqB = eqA /. b -> Sqrt[z]*a // Simplify[#, {a > 0, z > 0}] &

(*  y1^2 + x1^2 z == y2^2 + x2^2 z  *)

Equal @@ Solve[eqB, z][[1, 1]] /. z -> b^2/a^2

(*  b^2/a^2 == (-y1^2 + y2^2)/(x1^2 - x2^2)  *)

Have fun!

$\endgroup$
3
$\begingroup$
eq1 = x1^2/a^2 + y1^2/b^2 == 1;
eq2 = x2^2/a^2 + y2^2/b^2 == 1;
(SubtractSides[eq1, eq2] //
    Collect[#, {a, b}] &) /.
  (a_^2 - b_^2) :> (a + b) (a - b) /. {a_. b_ + c_. d_ == 0 -> 
   d/b == -(a/c)}

$$\frac{(\text{y1}-\text{y2}) (\text{y1}+\text{y2})}{(\text{x1}-\text{x2}) (\text{x1}+\text{x2})}=-\frac{b^2}{a^2}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.